RA Kartini's Thoughts on Women's Education and Its Relevance to Islamic Education - Nurlailli Hidayati; Fitri Wulandari (al-Afkar, Journal For Islamic Studies, 2025)
RA Kartini showed that she was a fighter in the field of feminism, namely by fighting for women's rights in working and gaining their rights as human beings through women's education with the main focus being training for writing, reading and sewing. The aim of education provided by women is to present and fight for gender equality and eradicate the culture of marginalization of women, gender equality is in the form of education, voicing the opinions and duties of women in society. Even though Kartini used to have limited religious understanding, Kartini believed that religion had a big role in society and human civilization. Kartini did not explicitly state the importance of religion in education in her letters, but Kartini's deeper understanding of religion provides a view that the basis of a child's education is a good religion, which is first given by a mother to a child in the product of temperament and character. Women's educational thoughts and practices towards the native community are a stimulant for the growth of better understanding and knowledge, especially in Islamic education. Kartini's criticality regarding the importance of women's education gave awareness to the ulama to increase understanding of Islam to the public with a clear educational concept. After Kartini's death, many Islamic schools were founded, not only open to boys but also girls.